E-276 Temporal change in enhancement of intracranial atherosclerotic plaques post gadolinium administration. (23rd July 2022) - Patel, A; Abdalla, R; Chaudhry, T; Shaibani, A; Cantrell, D; Jahromi, B; Potts, M; Ansari, S
Abstract : Introduction: Magnetic resonance vessel wall imaging is used to evaluate plaque activity in patients with intracranial atherosclerotic disease (ICAD). ICAD plaques are qualitatively compared to other intracranial tissues, and the degree of enhancement is used to differentiate between symptomatic and asymptomatic plaques. However, the optimum time for evaluating plaque enhancement after contrast injection is not standardized and may vary depending on the biodistribution of contrast in different cranial structures. We aim to assess contrast distribution in cranial/intracranial tissues and ICAD plaques at early (5 minutes) and delayed (20 minutes) post-contrast scans, qualitatively and quantitatively. Methods: IRB approval was obtained: Inclusion criteria were patients with confirmed ICAD plaques and pre-contrast, early post-contrast (5 minutes), and delayed post-contrast(20 minutes) T1-SPACE sequences. Standardized diameter (2 mm) regions of interest (ROIs) were used to evaluate the cavernous sinus (CS), temporalis (TM), pituitary infundibulum (PI), choroid plexus (CP), and intracranial plaques (ICAD-P). Measurements were acquired in pre-contrast, early post-contrast, and delayed post-contrast T1-SPACE sequences for each patient. Plaque enhancement was qualitatively assessed relative to the pituitary infundibulum. (0 = No enhancement, 1 = enhancement less than PI, 2= Enhancement equal to or more than PI). Means were compared using one-way repeated ANOVA in SPSS version (27) and p-value was set at 0.05. Results: 10/16 patients met all inclusion criteria. A total of 18 ICAD plaques were analyzed. Plaques and the reference structures demonstrated a statistically significant increase in signal intensity from pre-contrast scans to early post-contrast scans and delayed post-contrast scans on T1 SPACE sequence. While ICAD plaques demonstrated an increase in signal intensity in delayed vs early post-contrast T1 SPACE scans (P = 0.044 ), the PI demonstrated a decrease in signal intensity (P = 0.045). No statistically significant change in mean signal intensity was observed in the other reference structures. Conclusion: Contrast enhancement gradually increased in plaques from early to delayed post-contrast scans, as opposed to the pituitary infundibulum, which demonstrated a significant decrease, while other cranial structures showed no changes. This could lead to false positive plaque enhancement if judged qualitatively on delayed imaging especially if using pituitary infundibulum as reference/internal control. Disclosures: A. Patel: None. R. Abdalla: None. T. Chaudhry: None. A. Shaibani: None. D. Cantrell: None. B. Jahromi: None. M. Potts: None. S. Ansari: None.